PRIMARY RESONANCE OF THE BEARING ROTOR SYSTEM WEAK NONLINEAR ANALYSIS OF A MOTOR - YANG ZhiAn; MENG JiaJia (Jixie qiangdu)
Changing a bearing rotor system of a motor as object,consider eccentric force,oil-film force,unbalanced magnetic pull and asymmetric stiffness,applying Newton’s second law the weak nonlinear vibration equation of the bearing rotor system of a motor is established. By means of the averaging method of nonlinear vibration,the first approximation solutions and corresponding to stationary solutions of the parametric and forced vibration of the system are obtained,and the numerical calculation is carried out. The effect of the electromagnetic parameter on the response curves of the Primary resonance of the system is analyzed. With the increasing of the rotor radius,airtight magnetic gap and core length,the response curves of the Primary resonance of the system move to right hand.